Železobetonová konstrukce obytného domu - Čairović, Dorde (Vysoké učení technické v Brně. Fakulta stavební, 2013)
Diplomová práce je zamerena na návrh a posouzení hlavních části nosné železobetonové konstrukce obytného domu a to: monolitická stropní deska nad 2NP, základová deska, schodiště, sloup a stěna. Součásti práce je i výkresová dokumentace vybraných prvků. Výpocet vnitrních sil byl proveden v grafickém softwarovém systému Scia Engineer.

The master thesis is aimed for design and assessment of main bearing segments of reinforced concrete structure of apartment block: monolithic reinforced concrete slab over the second floor, foundation slab, stairway slab, pillar and wall beam. Constituent part of the thesis is also drawing documentation of reinforcement of selected segments. Calculation of the internal forces is made at graphical software system Scia Engineer.
Reinforced concrete structure of an apartment block
Keywords: železobetonová stropní deska; základová deska; schodiště; sloup; stěna; zatížení; zatežovací stavy; vnitrní síly; dimenzování; návrh betonárské výztuže; výkresová dokumentace; Reinforced concrete slab; foundation slab; stairway slab; pillar; wall beam; load; load cases; internal forces; design of structures; design of reinforcement; drawing documentation